Del Portal en La Comunicación Empresarial a La Web 2.0. La Carrera por La Empatía con El Usuario - Barroso Huertas, Óscar (Re-presentaciones: Periodismo, comunicación y sociedad, 2008)
In this article, the present relevance of the Corporative Website within the newest Business Communication concept is analyzed when applied to the empathy with its stakeholders, in the Communication strategy that tries to be efficient in the Web 2.0 frame. The use of Internet as an approaching tool of the Company to its stakeholders, implies an adaptation, not only in accesibility to the information but also in its attractiveness for the user, indeed.
Keywords: Business Communication; Corporate Communication; Corporative Website; Internet; Web 2.0.